With sensitive eyes: ECEC teachers’ visual gaze and related reflections on pedagogical actions in toddler groups using eye-tracking glasses - Ukkonen-Mikkola, Tuulikki; Isotalo, Susanna; Chaudhuri, Saswati; Salminen, Jenni; Merjovaara, Olli; Lindén, Carita; Rutanen, Niina (Frontline Learning Research, 2024)
This study explored early childhood education and care (ECEC) teachers’ visual gaze and related reflections on pedagogical actions during pedagogical activities in groups of children under three years of age in Finland. The data were collected from play and teacher-guided activities using mobile eye-tracking glasses, the retrospective thinking aloud (RTA) method, and semi-structured interviews. The results showed that even though the teachers were surprised about some aspects of the visual gaze metrics, they reflected on and gave reasons for their visual gazes on children. When observing gaze data from play, teachers explained the high amount of gaze by citing children’s particular needs. When observing gaze data from guided activities, teachers reflected on children’s unpredictable behavior and noted that the children’s need for support in concentration was linked to more gazes by the teacher. The findings showed that both during play and guided activities, children seeking a gaze and the position of children in the classroom influenced the number of teachers’ gazes. In the teachers’ explanations of their visual gaze and related pedagogical actions, five categories were identified: protection; physical and emotional availability, teaching and learning; facilitation; and initiatives. This explorative study showed that teachers utilize their knowledge concerning children’s individuality, development, and learning when they explain their decisions concerning their visual gaze and pedagogical activities with toddlers. The use of mobile eye-tracking technology is relatively new; therefore, its applications to ECEC are pioneering for the development of the field in relation to the practices and research of toddlers’ groups and groups with older children in ECEC